Proposta de framework para adoção de IoT no gerenciamento de uma cadeia de suprimentos da indústria de autopeças - Guerhardt, Flávio (2019)
Supply Chain Management (GCS) is in constant technological development. An example of this can be seen in the advancement of Information Technology (IT) and the Internet of Things (IoT - connected objects exchange information between themselves autonomously). The use of IoT is progressively expanding in the industrial area, however there is no evidence of Frameworks for the application of IoT in GCS, as well as research aimed at Auto Parts Companies using IoT technology in GCS. The purpose of this thesis is the development and presentation of a Framework that will serve as a guide for implementing IoT in GCS. To this end, a literature review was conducted to identify the research gap and assist the construction of the Framework. To validate the applicability of such Framework, using the Delphi tool, opinions were collected from experts located in Auto Parts Companies belonging to a given Supply Chain . The result shows that respondents considered the proposed Framework feasible, reliable and secure, as it brings rapid decision, process transparency, cost minimization and, consequently, better resource management in Supply Chain Management.